What W.H. Auden Can Do for You. - McCall Smith, Alexander, 1948- (Writers on writers., 2013)
When facing a moral dilemma, Isabel Dalhousie--Edinburgh philosopher, amateur detective, and title character of a series of novels by best-selling author Alexander McCall Smith--often refers to the great twentieth-century poet W.H. Auden. This is no accident: McCall Smith has long been fascinated by Auden. Indeed, the novelist, best known for his No. 1 Ladies Detective Agency series, calls the poet not only the greatest literary discovery of his life but also the best of guides on how to live. In this book, McCall Smith has written a charming personal account about what Auden has done for.